Ethylene Glycol Mediated, Catalyst-Free Synthesis of Bis(pyrazolo) pyridines and Their Photophysical Studies - Shanthi, Markabandhu; Janani, Ravichandran; Puhazhendhi, Arulmozhi; Shankar, Bhaskaran; Sivalingam, Soumya; Ramesh, Subburethinam (Synthesis, 2024)
A new hetero-annulation procedure for the selective synthesis of bis(pyrazolo)-fused pyridines using pyrazole-5-amines and aryl glyoxal monohydrate is described. This distinct hetero-annulation, carried out under catalyst-free conditions with ethylene glycol as the medium, illustrates a domino reaction that involves the formation of two C–C bonds and one C–N bond. The photophysical properties of the synthesized derivatives were briefly analyzed. The emission spectra of the derivatives exhibited distinct charge transfer peaks, which depends on the structure of the derivatives. The green metrics calculation for the protocol to quantify the waste, reaction efficiency, and sustainability was evaluated.
Keywords: bis(pyrazolo)pyridines; metal free; ethylene glycol; pyrazolopyridine